Education Fair: Layanan Bimbingan Karier dalam Perencanaan Studi Lanjut Siswa di Tumbuh High School - Ferra Puspito Sari (Lembaga Sosial Rumah Indonesia, 2022)
Student problems related to planning for further studies require career guidance services from guidance and counseling teachers at schools. Tumbuh High School, through the Education Fair program, seeks to assist students in the process of planning further studies. This study aims to describe and analyze the application of education fair as a career guidance service in planning for further studies for Tumbuh High School students. This study uses descriptive qualitative research methods, data collection through interviews, observation, and documentation. The subjects in this study were school principals, guidance and counseling teachers, parents, and Tumbuh High School students who were involved in and affected by the education fair program. The results of this study indicate that the education fair held at Tumbuh High School begins with an in-depth assessment to determine the talents and interests of students, the selection of universities or partner institutions according to the results of the assessment, the implementation of the educational fair by partner institutions attended by students and their parents; and evaluation of implementation. Students are more mature in planning a career related to studies based on their talents and interests.